Screening and quantification of dichlorodiphenyltrichloroethane (DDT) and Dichlorovos in selected dry fish species of Bangladesh by GC-ECD detector (International Journal of Scientific Research and Management (IJSRM), 2013)
An attempt was made to know the residual status of insecticides in dry fish during their long term preservation by Electron Capture Detector (ECD) of Gas Chromatography. Eleven popular fish species were selected and samples were collected from different markets of Sayedpur and Cox’s bazar of Bangladesh. All samples were extracted and prepared for injection using standard protocols for residue analysis during November to February 2012. The DDT concentration ranges were found of 14.454 to 1249.686 ppb according to 209.185 755.032 ppb for ribbon fish, 262.185 485.809 ppb for bombay duck, 242.166 298.165 ppb for giant perch, 161.739 515.185 ppb for prawn, 146.886 487.102 ppb for needlefish, 34.279 204.403 ppb for puntio barb, 111.495 420.191 ppb for snakehead (taki & shol), 587.146 1249.686 ppb for freshwater shark (Shol) and 14.454 97.124 ppb for freshwater shark (Boal), respectively. Samples collected from Sayedpur, DDT was found of 33.498 ppb for Chinese pomfret and 370.461 ppb for striped dwarf catfish, not at all found in cox’s bazar samples. No Dichlorovos residues were detected in all the samples. However, the residual DDT ranges within the safe limit, efforts should be given on limiting the uses of all classes of hazardous chemicals for avoiding any health hazard situation and ensuring food security.